PELATIHAN SOAL HOTS (HIGHER ORDER THINGKING SKILL) BERBASIS KEMAMPUAN BERPIKIR KRITIS BAGI GURU MATEMATIKA KOTA SUNGAI PENUH - Handican, Rhomiy; Lutfi, Ahmad; andriani, Cici; Aryani, Letty (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2024)
Training on HOTS (Higher Order Thinking Skills) based on critical thinking skills for mathematics teachers in Sungai Penuh City is an important effort to enhance the quality of mathematics education in the region. This training aims to equip teachers with skills in designing and presenting HOTS questions that effectively develop students' critical thinking abilities. Through interactive and participatory learning approaches, this training helps teachers understand the importance of developing critical thinking skills in mathematics education. By focusing on implementing active learning strategies and utilizing technology in teaching, this training provides practical guidance for teachers to enhance their skills in designing challenging and relevant learning experiences. The results of this training show a significant improvement in the abilities of both teachers and students to design, implement, and evaluate HOTS questions, as well as enhance students' academic achievements in mathematics. Therefore, HOTS-based training on critical thinking skills is a crucial step in improving the quality of mathematics education in Sungai Penuh City.